Epidemiological profile of patients with malignant neoplasm admitted to a tertiary care center in India: a retrospective cross-sectional study - Debnath, Sourav; Pal, Pusparghya; Singh, Anurag Kumar; Mishra, Shivang; Rajotiya, Sumit; Ghosh, Manashi; Nakash, Prashant; Kumar, Sachin; Singh, Roshni; Sharma, Govind; Singh, Mahaveer; Nathiya, Deepak; et al. (Frontiers in Oncology, 2025)
BackgroundCancer poses a growing public health challenge in India, with significant urban–rural disparities in diagnosis and treatment. This study aimed to evaluate the epidemiological profile and treatment patterns of cancer patients in Rajasthan, focusing on differences in disease presentation, treatment modalities, and outcomes between urban and rural populations.MethodsA retrospective observational study was conducted at the National Institute of Medical Sciences and Research, Jaipur, including 1,366 histopathologically confirmed cancer patients admitted between January 2021 and December 2023. Data on demographics, cancer type, stage, treatment, and outcomes were analyzed using SPSS version 28, comparing rural and urban groups.ResultsOf the 1,366 patients, 77.45% were from rural areas. Rural patients had higher rates of advanced-stage (Stage IV) presentation (56.1% vs. 47.7%, p = 0.047) and tobacco use (16.8% vs. 10.4%, p = 0.006). Head and neck cancers were most common in men (20.7%), and breast cancer in women (8.2%). Chemotherapy was the predominant treatment (84%) modality, while urban patients more frequently received multimodal therapy. In-hospital mortality was comparable between groups (4.82% vs. 4.22%, p = 0.661), as were readmission rates.ConclusionRural patients experienced a greater cancer burden due to delayed diagnosis and limited access to comprehensive care. Strengthening rural oncology services, improving early detection, and addressing modifiable risk factors like tobacco use are critical for reducing disparities and improving outcomes.